PENGEMBANGAN E-MODUL MENGGUNAKAN FLIPBOOK PADA TEMA 9 SUBTEMA 1 BENDA TUNGGAL DAN CAMPURAN - Lulu Maulidah; Dadang Kurnia; Fitri Anjaswuri (STKIP Subang, 2023)
This study aims to develop e-modules using flipbooks learners understands learning materials, increase student’ interest and learning motivation, then help teachers to be able to innovate in developing teaching materials in digital form like the e-module using a flipbook. this study uses the research and development method with the ADDIE approach. This research was conducted in five stages, namely the stages of needs analysis, design, development, implementation, and evaluation. The subjects of this study were VB class at SD Negeri Pajajaran consisting 28 students. The research was conducted in the even semester of the 2022/2023 school year. The results of this study indicate that the e-module using the flipbook that has been developed is very feasible. This is based on the percentage of media experts 97%, linguists experts 97%, material experts 96%, and student responses 92%. Based on this, it can be concluded that e-modules using flipbooks on the theme 9 sub-themes 1 single and mixed objects that are developed are very feasible to use during the learning activity process.